Aerosol chemistry, transport, and climatic implications during extreme biomass burning emissions over the Indo-Gangetic Plain - Singh N.; Banerjee T.; Raju M.P.; Deboudt K.; Sorek-Hamer M.; Singh R.S.; Mall R.K. (My University, 2025)
The large-scale emissions of airborne particulates from burning of agricultural residues particularly over the upper Indo-Gangetic Plain (IGP) have often been associated with frequent formation of haze, adverse health impacts, and modification in aerosol climatology and thereby aerosol impact on regional climate. In this study, short-term variations in aerosol climatology during extreme biomass burning emissions over the IGP were investigated. Sizesegregated particulate concentration was initially measured and submicron particles (PM1:1) were found to dominate particulate mass within the fine mode (PM2:1). Particulatebound water-soluble ions were mainly secondary in nature and primarily composed of sulfate and nitrate. There was evidence of gaseous NH3 dominating neutralization of acidic aerosol species (SO2- 4 ) in submicron particles, in contrast to crustal-dominating neutralization in coarser particulates. Diurnal variation in black carbon (BC) mass ratio was primarily influenced by regional meteorology, while gradual increase in BC concentration was consistent with the increase in Delta-C, referring to biomass burning emissions. The influence of biomass burning emissions was established using specific organic (levoglucosan), inorganic (K+ and NH+ 4), and satellite-based (UV aerosol index, UVAI) tracers. Levoglucosan was the most abundant species within submicron particles (649±177 ngm-3), with a very high ratio (> 50) to other anhydrosugars, indicating exclusive emissions from burning of agriculture residues. Spatiotemporal distribution of aerosol and a few trace gases (CO and NO2) was evaluated using both spaceborne active and passive sensors. A significant increase in columnar aerosol loading (aerosol optical depth, AOD: 0.98) was evident, with the presence of absorbing aerosols (UVAI > 1.5) having low aerosol layer height (∼1:5 km). A strong intraseasonality in the aerosol cross-sectional altitudinal profile was even noted from CALIPSO, referring to the dominance of smoke and polluted continental aerosols across the IGP. A possible transport mechanism of biomass smoke was established using cluster analysis and concentration-weighted air mass back trajectories. Short-wave aerosol radiative forcing (ARF) was further simulated considering intraseasonality in aerosol properties, which resulted in a considerable increase in atmospheric ARF (135Wm-2) and heating rate (4.3Kday-1) during extreme biomass burning emissions compared to the non-dominating period (56Wm-2, 1.8Kday-1). Our analysis will be useful to improve understanding of short-term variation in aerosol chemistry over the IGP and to reduce uncertainties in regional aerosol-climate models. © 2018 Author(s).